2008
DOI: 10.1038/ncb1694
|View full text |Cite
|
Sign up to set email alerts
|

Control of daughter centriole formation by the pericentriolar material

Abstract: Controlling the number of its centrioles is vital for the cell as supernumerary centrioles result in multipolar mitosis and genomic instability 1,2 . Normally, just one daughter centriole forms on each mature (mother) centriole 3,4 ; however, a mother centriole can produce multiple daughters within a single cell cycle 5,6 . The mechanisms that prevent centriole 'overduplication' are poorly understood. Here we use laser microsurgery to test the hypothesis that attachment of the daughter centriole to the wall of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
213
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(229 citation statements)
references
References 30 publications
14
213
2
Order By: Relevance
“…New centriole assembly appears to be controlled at the level of the centrioles and surrounding PCM. Consistent with this notion, increasing the size of the PCM by pericentrin overexpression allows assembly of multiple procentrioles near the mother centriole [81].…”
Section: Centriole Duplication: Only One Daughtersupporting
confidence: 62%
“…New centriole assembly appears to be controlled at the level of the centrioles and surrounding PCM. Consistent with this notion, increasing the size of the PCM by pericentrin overexpression allows assembly of multiple procentrioles near the mother centriole [81].…”
Section: Centriole Duplication: Only One Daughtersupporting
confidence: 62%
“…Therefore, another function of the centriolar adjunct could be to promote the formation of a second centriole in the vicinity of the centriole/basal body. In support of this idea, recent studies have shown that PCM promotes new centriole assembly, perhaps by concentrating ␥-tubulin (Dammermann et al, 2008;Loncarek et al, 2008).…”
Section: Bld10 Is a Conserved Centriolar Proteinmentioning
confidence: 62%
“…12,13 Pericentrin overexpression caused expansion of the PCM, allowing the formation of multiple daughter centrioles independently of any spatial or numerical control from the mother centrioles. 14 This observation prompted the hypothesis that the mother centriole's principal role in centriole assembly is the regulation and specification of a PCM scaffold, rather than the provision of a template. 14 Loss-of-function analyses of pericentrin have demonstrated roles for the protein in controlling centrosome functions during both mitosis and interphase.…”
Section: Introductionmentioning
confidence: 99%
“…14 This observation prompted the hypothesis that the mother centriole's principal role in centriole assembly is the regulation and specification of a PCM scaffold, rather than the provision of a template. 14 Loss-of-function analyses of pericentrin have demonstrated roles for the protein in controlling centrosome functions during both mitosis and interphase. Injection of anti-pericentrin antibodies disrupted mitotic spindle formation in frog embryos.…”
Section: Introductionmentioning
confidence: 99%